Tumor biology and multidisciplinary strategies of oligometastasis in gastrointestinal cancers. (February 2020) - Zhao, Yue; Li, Jiahui; Li, Dai; Wang, Zhefang; Zhao, Jiangang; Wu, Xiaolin; Sun, Qiye; Lin, Peter Ping; Plum, Patrick; Damanakis, Alexander; Gebauer, Florian; Zhou, Menglong; et al.
Abstract: More than 70% of gastrointestinal (GI) cancers are diagnosed with metastases, leading to poor prognosis. For some cancer patients with limited sites of metastatic tumors, the term oligometastatic disease (OMD) has been coined as opposed to systemic polymetastasis (PMD) disease. Stephan Paget first described an organ-specific pattern of metastasis in 1889, now known as the "seed and soil" theory where distinct cancer types are found to metastasize to different tumor-specific sites. Our understanding of the biology of tumor metastasis and specifically the molecular mechanisms driving their formation are still limited, in particular, as it relates to the genesis of oligometastasis. In the following review, we discuss recent advances in general understanding of this metastatic behavior including the role of specific signaling pathways, various molecular features and biomarkers, as well as the interaction of carcinoma cells with their tissue microenvironments (both primary and metastatic niches). The unique features that underlie OMD provide potential targets for localized therapy. As it relates to clinical practice, OMD is emerging as treatable with surgical resection and/or other local therapy options. Strategies currently being applied in the clinical management of OMD will be discussed including surgical, radiation-based therapy, ablation procedures, and the results of emerging clinical trials involving immunotherapy.